Litter Fall and Natural Regeneration of Spruce and Silver Fir - Bhagat, Virendra Singh. S.; Arya, S. R. (Indian Forester, 1987)
The litler fall in the mixed forest of si1ver fir and spruce waS studied for a period of three years. The maximum annual litter fall varied from 5260.6 to 5173.0 kg/ha/yr in different experimental plots. The litter accummulation has adverse effect on natural regeneration of silver fir and spruce.